2016
DOI: 10.1016/j.cplett.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring changes of paramagnetically-shifted 31P signals in phospholipid vesicles

Abstract: Phospholipid vesicles are commonly used as biomimetics in the investigation of the interaction of various species with cell membranes. In this paper we present a 31 P NMR investigation of a simple vesicle system using a paramagnetic shift reagent to probe the inner and outer layers of the lipid bilayer. Time-dependent changes in the 31 P NMR signal are observed, which differ whether the paramagnetic species is inside or outside the vesicle, and on the choice of buffer solution used. An interpretation of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 43 publications
(57 reference statements)
1
13
0
Order By: Relevance
“…Lanthanides have previously been shown to interact with the phospholipid head group region. 6,63 An increased head group mobility would enable a greater number of lanthanide ions to interact. This may have less of an impact on Dy 3+ in comparison to Yb 3+ due to size differences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lanthanides have previously been shown to interact with the phospholipid head group region. 6,63 An increased head group mobility would enable a greater number of lanthanide ions to interact. This may have less of an impact on Dy 3+ in comparison to Yb 3+ due to size differences.…”
Section: Resultsmentioning
confidence: 99%
“…In the latter application, lanthanide ions applied externally to extruded phospholipid vesicles are used to distinguish between the signal from the inner and outer lipids of the membrane. 5,6 The difference in signal is attributed to lanthanide induced chemical shifts in the NMR signal from the outer head groups of the vesicle. By monitoring the change in this signal over time the intrinsic rate of lipid flip-flop within a model membrane system can be quantified.…”
Section: Introductionmentioning
confidence: 99%
“…The large increase in the flip-flop rates and activation energies under salt conditions, might be important to rationalise NMR experiments that use ytterbium salts to access the lipid dynamics. 17,19,44 There are several lines of future enquiry stemming from our work. Since we have used a well defined membrane compositions, our results should motivate controlled experiments to verify the conclusions presented in this work.…”
Section: Resultsmentioning
confidence: 97%
“…Such effect would be important to understand the role of salt on membrane biophysics as well as to interpret experimental results obtained with different experimental techniques. [14][15][16][17] In our previous work, 18 we demonstrated that Yb 3+ ions modify significantly the membrane rigidity and the orientation of the lipid head group. The question we wish to address in this work is whether the interactions of physiological relevant cations, Na + , K + , Mg 2+ , Ca 2+ and ions employed in NMR experiments, Yb 3+ , might modify the lipid flip-flop translocation rates.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation